The product of the adenovirus intermediate gene IX is a transcriptional activator. - Lutz, P (1997)
We have investigated the functional properties of the product of the adenovirus type 5 gene IX. This gene, which is expressed at intermediate times postinfection, encodes a small polypeptide (pIX) of 140 residues that has previously been shown to be incorporated into the viral capsid. Here, we show that pIX, in addition to its structural contribution, exhibits transcriptional properties. In transient transfection experiments, expression of pIX stimulated adenovirus major late promoter activity. The effect was independent of other viral proteins, but the level of promoter activation appeared strongly pIX dose dependent; similar levels of induction were observed with other cellular or viral TATA-containing (but not with TATA-less) promoters. This promoter specificity could be reproduced in a cell-free transcription system by the addition of purified recombinant pIX, further stressing the transcriptional nature of the phenomenon. A preliminary structural analysis of pIX indicated that the integrity of a putative leucine zipper at the carboxy-terminal end of the molecule, as well as elements within the amino-terminal half, was critical for pIX transcriptional activity. The relevance of these findings in adenovirus infection is discussed.